Correction: An RT-PCR panel for rapid serotyping of dengue virus serotypes 1 to 4 in human serum and mosquito on a field-deployable PCR system - Tsai, Jih-Jin; Liu, Wei-Liang; Lin, Ping-Chang; Huang, Bo-Yi; Tsai, Ching-Yi; Chou, Pin-Hsing; Lee, Fu-Chun; Ping, Chia-Fong; Alison Lee, Pei-Yu; Liu, Li-Teh; Chen, Chun-Hong (PloS one, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0214328.].